THE ISLAMIC EDUCATION STRATEGIES INLOCAL CULTURE PERSPECTIVE OF WEST SUMATERA SOCIETY - Zulfani Sesmiarni; Junaidi Junaidi; Darul Ilmi; Wedra Aprison (Jurnal Educative: Journal of Educational Studies, 2018)
Sijunjung is one of regencies in West Sumatera which has great potential resources. However, these graces are not followed by the society’s thankfulness through performing Islamic values. Based on the fact, the researchers were interested to do a research related to Islamic education strategies in local culture perspective in Koto VII sub-district Sijunjung regency. The research was aimed at helping the society to be aware of making the best use of the potential things and thanks God through performing Islamic values and avoiding all God’s prohibitions. The research included some elements they were Tali Tigo Sapilin which consisted of niniak mamak, alim ulama and cadiak pandai, the youth, and adults. The research was in Focus Group Discussion. The research finding was that Minangkabau philosophy in west Sumatera was in line with Islamic education strategies in Kitabullah.